Environmental scan of librarian involvement in uOttawa systematic & scoping reviews - Farrell, Peter; Cole, Victoria; DaSilva, Emily; Ly, Valentina; Sterling, Evan; Dehler, Nicholas; El Hofi, Alain; Rokolj, Téa; Visintini, Sarah; Labelle, Patrick; Sikora, Lindsey (Université d'Ottawa | University of Ottawa, 2023)
Introduction: Requests for librarian collaboration on knowledge synthesis projects at the University of Ottawa have increased over time. Despite having significant impact on workload, the intellectual contributions of librarians are not always recognized through authorship or acknowledgement. We conducted an environmental scan to establish a baseline for how librarian involvement is reported in all systematic and scoping reviews published by authors affiliated with the University of Ottawa. Specifically, we wanted to better understand the publication volume, workload implications, and extent of reported librarian involvement. Methods: We searched 18 databases across various subject areas. Keyword and publication-type searches were combined with affiliation searches for the University of Ottawa or affiliated research institutes/centres. Published systematic reviews, scoping reviews, meta-analyses, and published protocols for these methodologies were included. All other review methodologies were excluded. Data extraction focused on bibliographic information, librarian involvement, funding, uOttawa affiliation, and the type of review. (Protocol available here: https://osf.io/bqd26/) Results: Search results yielded 20,270 records. After duplicates were removed, 8,805 records were screened by title and abstract. 6,049 records passed to full-text screening (currently underway). Preliminary results show reviews from a greater diversity of disciplines than originally anticipated. Consistency of review nomenclature varies greatly between disciplines and poses a challenge in ensuring consistency during screening. Discussion: This environmental scan maps systematic and scoping review publications across disciplines at the University of Ottawa. Better understanding the proportion of reviews with librarian involvement will help guide policy and procedure development around knowledge synthesis services, and enable us to project resourcing needs in the future.
Keywords: Scoping Reviews; Systematic Reviews; Library collaboration; Knowledge synthesis